Analisis Penilaian Tingkat Kesehatan Koperasi Simpan Pinjam Dan Pembiayaan Syariah Al Uswah Indonesia Kota Banjar - Nanang Sobarna (Coopetition : Jurnal Ilmiah Manajemen, 2020)
This study aims to analyze the level of health of the Koperasi Simpan Pinjam dan Pembiayaan Syariah Al Uswah Indonesia Kota Banjar in 2019. This study uses quantitative methods with health assessment analysis with health research analysis guided by the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and UKM No. 07 / Per / Dep.6 / IV / 2016. concerning Guidelines for Health Assessment of Sharia Savings and Loans and Financing Cooperatives and Sharia Financing Savings and Loans Units. Based on the results of research on 8 aspects of assessing the health level of savings and loan cooperatives and sharia financing at the Al Uswah Indonesia KSPPS Banjar City in 2019, it is at the predicate of the level of health under supervision.